Problem-Based Learning Implementation: Improvement in Learning Process and Results in Vocational Higher Education - Muhammad Nurtanto; Soffan Nurhaji; Jamil Abd Baser; Yadin Yadin (Faculty of Engineering, Universitas Negeri Yogyakarta, 2018)
Problem Based Learning (PBL) is a learning method considered to be capable of changing the students’ perception in facing the challenges of the 21st century. This study was aimed to improve soft skills in the form of critical thinking, motivation, and group dynamics and hard skills in the form of psychomotor ability by applying PBL. This study was designed with an action research design. The research subjects were 30 students at the age of 19 to 22 years old. Data were collected with performance appraisal, observation sheet and questionnaires. The results indicated that (1) the students’ critical thinking works effectively during problem identification and problem hypothesis, (2) increasing motivational ability indicated by time discipline, and (3) improved group dynamics skills during group discussions and groups activities. The results for psychomotor ability showed an increase of 16.6 or 17%. This confirmed that PBL improved the students’ soft skills and hard skills reflected in positive and effective group activities.